Impacts of systemic inflammation response index on the prognosis of patients with ischemic heart failure after percutaneous coronary intervention - Ma, Meishi; Wu, Kang; Sun, Tienan; Huang, Xin; Zhang, Biyang; Chen, Zheng; Zhao, Zehao; Zhao, Jiajian; Zhou, Yujie (Frontiers in Immunology, 2024)
Background Atherosclerosis and cardiovascular diseases are significantly affected by low-grade chronic inflammation. As a new inflammatory marker, the systemic inflammation response index (SIRI) has been demonstrated to be associated with several cardiovascular disease prognoses. This study aimed to investigate the prognostic impact of SIRI in individuals having ischemic heart failure (IHF) following percutaneous coronary intervention (PCI). Methods This observational, retrospective cohort study was conducted at a single site. Finally, the research involved 1,963 individuals with IHF who underwent PCI, with a 36-month follow-up duration. Based on the SIRI quartiles, all patients were classified into four groups. Major adverse cardiovascular events (MACEs) were the primary outcomes. Every element of the main endpoint appeared in the secondary endpoints: all-cause mortality, non-fatal myocardial infarction (MI), and any revascularization. Kaplan–Meier survival analysis was conducted to assess the incidence of endpoints across the four groups. Multivariate Cox proportional hazards analysis confirmed the independent impact of SIRI on both the primary and secondary endpoints. The restricted cubic spline (RCS) was used to assess the nonlinear association between the SIRI and endpoints. Subgroup analysis was performed to confirm the implications of SIRI on MACE in the different subgroups. Results The main outcome was much more common in patients with a higher SIRI. The Kaplan–Meier curve was another tool that was used to confirm the favorable connection between SIRI and MACE. SIRI was individually connected to a higher chance of the main outcome according to multivariate analyses, whether or not SIRI was a constant [SIRI, per one−unit increase, hazard ratio (HR) 1.04, 95% confidence interval (95% CI) 1.01–1.07, p = 0.003] or categorical variable [quartile of SIRI, the HR (95% CI) values for quartile 4 were 1.88 (1.47–2.42), p <0.001, with quartile 1 as a reference]. RCS demonstrated that the hazard of the primary and secondary endpoints generally increased as SIRI increased. A non-linear association of SIRI with the risk of MACE and any revascularization (Non-linear P <0.001) was observed. Subgroup analysis confirmed the increased risk of MACE with elevated SIRI in New York Heart Association (NYHA) class III–IV (P for interaction = 0.005). Conclusion In patients with IHF undergoing PCI, increased SIRI was a risk factor for MACE independent of other factors. SIRI may represent a novel, promising, and low-grade inflammatory marker for the prognosis of patients with IHF undergoing PCI.